Development of Learning Media for Motorcycle Chassis Training Kit - Nurcholish Arifin Handoyono (Journal of Vocational Education Studies, 2021)
This research aims to determine the development process and the feasibility of learning media for motorcycle chassis training kit at SMK Muhammadiyah 1 Bambanglipuro. The type of research used is R&D. The research subjects were 32 students of class X TBSM SMK Muhammadiyah 1 Bambanglipuro. The data collection instruments used observation and questionnaires. The data analysis technique used the evaluation criteria analysis to determine the feasibility of learning media. The results showed that: (1) The development process went through several stages, namely: (a) problem background; (b) problem identification; (c) development ideas; (d) pre-production stage (tools and materials); (e) production stage; (f) product development; (g) validation and revision; (h) feasibility test; and (i) wearable products; and; (2) Learning media for motorcycle chassis training kit are categorized as very suitable for use in learning with the results of validation of media experts by 90%, material experts by 95%, small group trial of 85.24%, and large group trial of 83.94%.